The The Implementation of Student Worksheet Based on Contextual Teaching Learning on Ecosystem Materials to Train Scientific Process Skill for Students of Grade X Senior High School - Ardhita Filja Nurismawati; Sunu Kuntjoro (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
The worksheet that common used in schools only refers to cognitive assessment, especially at SMAN 2 Lamongan. In the independent learning curriculum, it is not enough to only required knowledge and attitude competencies, but skill competencies. Therefore, alternative learning that can solve the problem is learning by applying Contextual Teaching Learning-based worksheets to train students science process skills in Ecosystem material for grade X SMAN 2 Lamongan, which is adapted from the worksheet developed by Rosa (2020). This study aims to describe 1) the implementation of learning, 2) students science process skills, and 3) student responses. This research is a type of pre-experimental design research. The research target is 116 students of grade X SMAN 2 Lamongan. The parameters measured were 1) the implementation of learning, 2) students science process skills, and 3) student responses. The research data were analyzed according to the descriptive quantitative analysis method. The results showed 1) the implementation of learning carried out by the teacher was very good, 99.44%, 2) 93.75% of students had carried out science process skills very well and achieved completeness indicators, 3) student responses to worksheets were 97.22 % or very positive.